Autonomic Nervous System Responses to Concussion: Arterial Pulse Contour Analysis - La Fountaine, Michael F.; Toda, Michita; Testa, Anthony J.; Hill-Lombardi, Vicci (Frontiers in Neurology, 2016)
The arterial pulse wave (APW) has a distinct morphology whose contours reflect dynamics in cardiac function and peripheral vascular tone as a result of sympathetic nervous system (SNS) control. With a transition from rest to increased metabolic demand, the expected augmentation of SNS outflow will not only affect arterial blood pressure and heart rate, it will also induce changes to the contours of the APW. Following a sports concussion, a transient state cardiovascular autonomic dysfunction is present. How this state affects the APW, has yet to be described. A prospective, parallel-group study on cardiovascular autonomic control (i.e., digital electrocardiogram and continuous beat-to-beat blood pressure) was performed in the seated upright position in ten athletes with concussion and 7 non-injured control athletes. Changes in APW were compared at rest and during the first 60 seconds (F60) of an isometric handgrip test (IHGT) in concussed athletes and non-injured controls within 48 hours (48hr) and 1 week (1wk) of injury. The concussion group was further separated by the length of time until they were permitted to return to play (RTP>1wk; RTP≤1wk). SysSlope, an indirect measurement of stroke volume, was significantly lower in the concussion group at rest and during F60 at 48hr and 1wk; a paradoxical decline in SysSlope occurred at each visit during the transition from rest to IHGT F60. The RTP>1wk group had lower SysSlope (405±200; 420±88; 454±236 mmHg/s, respectively) at rest 48hr compared to the RTP≤1wk and controls. Similarly at 48hr rest, several measurements of arterial stiffness were abnormal in RTP>1wk compared to RTP≤1wk and controls: Peak-to-Notch Latency (0.12±0.04; 0.16±0.02; 0.17±0.05, respectively), Notch Relative Amplitude (0.70±0.03; 0.71±0.04; 0.66±0.14, respectively) and Stiffness Index (6.4±0.2; 5.7±0.4; 5.8±0.5, respectively). Use of APW revealed that concussed athletes have a transient increase in peripheral artery stiffness, which may be a compensatory adaptation to a paradoxical decline of stroke volume during the transition from rest to a state of increased metabolic demand within 48hr of concussion. This dysfunction of the SNS appeared to be more pronounced among concussed athletes who were removed from participation for >1 week compared to those who resumed play within 7 days.